2019
DOI: 10.3390/molecules24030627
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Specific Cucurbitadienol Synthase Allele in Siraitia grosvenorii Correlates with High Catalytic Efficiency

Abstract: Mogrosides, the main bioactive compounds isolated from the fruits of Siraitia grosvenorii, are a group of cucurbitane-type triterpenoid glycosides that exhibit a wide range of notable biological activities and are commercially available worldwide as natural sweeteners. However, the extraction cost is high due to their relatively low contents in plants. Therefore, molecular breeding needs to be achieved when conventional plant breeding can hardly improve the quality so far. In this study, the levels of 21 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…2,5 For example, some studies showed that the sweetest mogroside, S I, is 563 times sweeter than 5% sucrose solution, although this compound accounts for less than 5% of total MGs. 2,7,8 Moreover, unlike other types of sweet MGs with sweet profiles varying from that of sucrose, 9 the sweetness characteristics of S I were more similar to those of sucrose, without any aftertaste. 10 Several attempts have been made to develop procedures for obtaining S I, and most of them have focused on the transformation of MG V into S I.…”
Section: ■ Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…2,5 For example, some studies showed that the sweetest mogroside, S I, is 563 times sweeter than 5% sucrose solution, although this compound accounts for less than 5% of total MGs. 2,7,8 Moreover, unlike other types of sweet MGs with sweet profiles varying from that of sucrose, 9 the sweetness characteristics of S I were more similar to those of sucrose, without any aftertaste. 10 Several attempts have been made to develop procedures for obtaining S I, and most of them have focused on the transformation of MG V into S I.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Although there are several kinds of MGs in monk fruit, namely, MG VI, MG V, 11-oxo-MG V, MG IV, S I, MG III E, MG II, and MG I, few kinds are sweet. , For example, some studies showed that the sweetest mogroside, S I, is 563 times sweeter than 5% sucrose solution, although this compound accounts for less than 5% of total MGs. ,, Moreover, unlike other types of sweet MGs with sweet profiles varying from that of sucrose, the sweetness characteristics of S I were more similar to those of sucrose, without any aftertaste…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three intermediates (squalene, cucurbitadienol, and cycloartenol) were measured. The fruit samples for GC-MS analysis were prepared and the basic operational conditions were as described previously [13,33]. Helium gas was used as the carrier gas, and the carrier flow rate was 1.5 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the low content of mogrosides in LHG cannot meet the increasing market demand. Market surveys showed that the larger the fruit, the higher the price because of the high content (1%–2%, m / m ) of mogrosides in large LHG, and the extraction cost can be reduced by 1% when the mogroside content increases 0.1% [13]. Therefore, it is an urgent issue, taking some advanced technologies to achieve high-quality LHG.…”
Section: Introductionmentioning
confidence: 99%